Studi Ma’anil Hadis: Pemahaman Hadis Tirmidzi Nomor 1977 sebagai Antitesis Pencemaran Nama Baik di Media Sosial - Rangga, Rangga; Dalimunthe, Mahmud Jailani (AS-SABIQUN, 2023)
The use of social media often causes a person to fall into matters relating to the honor of other people, where a person freely behaves which in the end can violate existing laws that have been established. Cases of defamation are often found for social users, it is necessary to take a religious approach through the hadith of the prophet as an anticipation of defamation with the aim of reducing the cases of defamation that are rife. How is the contextualization of hadith in anticipation of defamation on social media. A qualitative research method with the type of Library Research examines data sources from the book of Sunan at-Tirmidzi, Tuhfatul Aswadzi and related law formulations. Then analyze with the study of Ma'anil Hadith. The results of the study show that there is significant significance in terms of the quality of sanad and matan, and the quantity of at-Tirmidzi hadith on defamation on social media can be accepted as an antithesis to reduce cases of defamation on social media. Then the contextualization of hadith as an anticipation of defamation on social media is a person whose faith is perfect by not damaging people's honor either through speech, writing or any media.